2004
DOI: 10.1007/s00702-004-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

The yield of laboratory investigations in children with infantile autism

Abstract: The only investigative study that contributed to the diagnosis of autistic infants was the molecular diagnosis detecting Fragile-X. In spite of the high frequency of epilepsy and epileptiform abnormalities in the electroencephalograms of autistic children in general, the contribution of epilepsy, both clinical and subclinical, to the etiology of autism is apparently minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…All of them have been performed on restricted cohorts of ASD patients. One study reported that none of the 53 patients with ASD, screened for ammonia, amino acids, lactic acid and pyruvic acid in blood and urinary organic acids, exhibited abnormal results [41]. Also, Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…All of them have been performed on restricted cohorts of ASD patients. One study reported that none of the 53 patients with ASD, screened for ammonia, amino acids, lactic acid and pyruvic acid in blood and urinary organic acids, exhibited abnormal results [41]. Also, Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] This range is applicable even for evaluations of patients with pervasive developmental disorder not otherwise specified, atypical autism, Asperger syndrome, or autistic features who did not necessarily meet the criteria of the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders criteria for pervasive developmental disorder. 21 Many factors seem to influence the diagnostic yield.…”
Section: Reported Approaches and Yieldsmentioning
confidence: 99%
“…Fragile X syndrome (FXS) is the most common single gene cause of ASD, responsible for approximately 3% of autism cases (Kosinovsky et al 2005). The prevalence rate of ASD in FXS is estimated between 25% and 50%, depending on the criteria utilized (Clifford et al 2007; Garcia-Nonell et al 2008; Hatton et al 2006; Kaufmann et al 2004).…”
Section: Introductionmentioning
confidence: 99%